2017
DOI: 10.3390/molecules22040561
|View full text |Cite
|
Sign up to set email alerts
|

Novel Palladium(II) Complexes that Influence Prominin-1/CD133 Expression and Stem Cell Factor Release in Tumor Cells

Abstract: New Pd(II) complexes of 1,7-bis(2-methoxyphenyl)hepta-1,6-diene-3,5-dione were synthesized and structurally characterized. The complexes were tested in vitro on human colon and hepatic carcinoma cell lines, normal hepatic cells and hematopoietic progenitor cells. Biological tests proved that Pd(II) complexes 1 and 2 (containing a curcumin derivative) exhibit a strong in vitro antitumor effect against the cells derived from human colorectal carcinoma and the hepatic metastasis of a colorectal carcinoma. Complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The Pd 2+ complex with curcumin derivative also exhibited a strong in vitro antitumor effect against human colorectal carcinoma and inhibited its hepatic metastasis. Furthermore, this complex has been shown to decrease tumor cell membrane expression of prominin-1 (CD133) molecules and restrict stem cell factor (SCF) release [65], which indicates its mechanism of antitumorigenesis and antimetastasis.…”
Section: Cancermentioning
confidence: 99%
“…The Pd 2+ complex with curcumin derivative also exhibited a strong in vitro antitumor effect against human colorectal carcinoma and inhibited its hepatic metastasis. Furthermore, this complex has been shown to decrease tumor cell membrane expression of prominin-1 (CD133) molecules and restrict stem cell factor (SCF) release [65], which indicates its mechanism of antitumorigenesis and antimetastasis.…”
Section: Cancermentioning
confidence: 99%
“…Palladium(II) complexes exhibited great cytotoxicity on human prostate cancer cells (DU145, LnCaP, PC3) which confirmed the potential of such organometallic derivatives to inhibit the tumor cell growth and to initiate the apoptosis [ 28 ]. Our previous research was also focused on the synthesis of palladium(II) complexes containing curcuminoids, which display a significant antiproliferative activity against several different human cancer cell lines [ 29 , 30 , 31 , 32 , 33 ]. Synthesized palladium complexes induced early and late apoptotic processes in colorectal cancer cells DLD-1 and HT-29 [ 30 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the treatment of lymphocytes with palladium complexes containing a curcumin derivative reveals an increase in the proportion of the T helper CD4 positive cell population, collateral with the decrease of T effector CD8 positive cells, and in the case of A2780 ovary cancer cells and HT-29 colon cancer cells, a significant cytotoxicity is detected [ 31 ]. Lastly, our research on palladium complexes containing the β-diketo moiety suggested that such compounds will not exert severe side effects as anticancer drugs, since they displayed a limited toxicity against normal, healthy cell populations such as colon epithelial cells [ 30 ], lymphocytes [ 31 ], and hepatocytes [ 33 ] in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work performed by members of our team focused on the synthesis of 15 natural‐identical curcumin analogs. These compounds were proved to be effective against human tumor cells, but they also exerted immunomodulatory properties on normal lymphocytes . For this study, we selected five of these compounds, based on their low cytotoxicity on tumor cells.…”
mentioning
confidence: 99%
“…The Knoevenagel condensates CurcK3, CurcK4, CurcK10, and CurcK11 proved to be intensely cytotoxic against HT‐29 colon carcinoma cells. The cytotoxic effect of the five synthetic curcumin analogs was associated with the increased cellular uptake and the regulation of intracellular enzymes implicated in oxidative stress .…”
mentioning
confidence: 99%